(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This article is co-authored and analyses the issues of student satisfaction with the format of online learning, their views on its future, and identifies the main difficulties with this format of learning. The authors have used the findings from 2021 questionnaires conducted in two universities in Poland and Ukraine, and from a 2022 questionnaire conducted at a university located in Georgia, which enlarged the geography of the study. Based on the survey results, the authors propose ways to solve the identified gaps in the online learning process. The article highlights possible practical use of the survey findings by transforming the current education model, adjusting the existing academic curriculum, making changes when preparing university classes, etc.